2022
DOI: 10.18203/2394-6040.ijcmph20222653
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health seeking behaviours for malaria treatment in Cameroon

Abstract: Background: Household health-seeking behaviour for malaria treatment is an important policy concern in malaria-endemic African countries. This paper aims to shed light on the determinants of household’s health-seeking behaviour for malaria treatment in Cameroon.Methods: The cross-sectional study used secondary data from the fourth Cameroonian household consumption survey conducted by the National Institute of Statistics. A stratified, 2-stage sampling was implemented with a sample of 918 households which sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Previous studies [23,25] have found association between higher education and timely seeking of treatment for suspected malaria infection in formal healthcare settings. Our study nding showed that many uneducated community members do not care about seeking care for suspected malaria infection from the hospital which is in tandem with what previous studies [23,34] have found out. It is more likely that the uneducated will have low health literacy and so they may not be aware of appropriate settings to treat their malaria related illness [35].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies [23,25] have found association between higher education and timely seeking of treatment for suspected malaria infection in formal healthcare settings. Our study nding showed that many uneducated community members do not care about seeking care for suspected malaria infection from the hospital which is in tandem with what previous studies [23,34] have found out. It is more likely that the uneducated will have low health literacy and so they may not be aware of appropriate settings to treat their malaria related illness [35].…”
Section: Discussionsupporting
confidence: 87%
“…Our study also revealed that age, group, gender, marital status and occupation were key determinant of observed knowledge which influenced practices that were observed. This is contrary to (Nounouce et al, 2022) where the level of education was a key determinant factor of a household health seeking behaviour. A study in Turkey by Abudu et al (2022) reported that participants were instead worried about the cost of treatment as a key factor to have influence patients seeking healthcare.…”
Section: Participants' Health Seeking Behavioursmentioning
confidence: 60%
“…We observed that 6% of the patient co-infected with intestinal coccidian diseases had simple malaria compared to 94% with severe malaria. Delay between onset of malaria and coccidian diseases and seeking healthcare is sufficient to increase the seriousness of the illness and death since malaria has the capacity to kill within hours of onset of symptoms (Nounouce et al, 2022).…”
Section: Participants' Health Seeking Behavioursmentioning
confidence: 99%